Transitioning to the National Institutes of Health single institutional review board model: Piloting the use of the Streamlined, Multi-site, Accelerated Resources for Trials IRB Reliance. (June 2019) - Vardeny, Orly; Hernandez, Adrian F; Cohen, Lauren W.; Franklin, Amy; Baqai, Mina; Palmer, Sarah; Bierer, Barbara E; Cobb, Nichelle
Background/Aims: Obtaining ethical approval from multiple institutional review boards is a long-standing challenge to multi-site clinical trials and often leads to significant delays in study activation and enrollment. As of 25 January 2018, the National Institutes of Health began requiring use of a single institutional review board for US multi-site trials. To learn more and further inform the research and regulatory communities around aspects of transitioning to single institutional review board review, this study evaluated the efficiency, resource use, and user perceptions of a nascent institutional review board reliance model (Streamlined, Multi-site, Accelerated Resources for Trials IRB Reliance). Methods: This research was embedded within the Influenza Vaccine to Effectively Stop Cardio Thoracic Events and Decompensated Heart Failure trial—a multi-site trial of two influenza vaccine formulations. In the first year of the trial, a sample of sites agreed to use the developing Streamlined, Multi-site, Accelerated Resources for Trials IRB Reliance model and participated in its evaluation. In keeping with a least burdensome approach, short surveys were developed and obtained from each reporting entity (relying sites, non-relying site, lead site, and reviewing institutional review board). Data regarding time to institutional review board approval and site activation, costs, and user perceptions of reliant review were self-reported and collected via the survey form. Quantitative and qualitative analyses were performed, with costs analyzed as actual versus estimated due to the lack of established baseline cost data. Results: A total of 13 sites ceded review and received institutional review board approval. Mean time to approval was substantially faster in sites that ceded review using the Streamlined, Multi-site, Accelerated Resources for Trials IRB Reliance model versus the site that did not cede review (81 vs 121 days). The mean time to approval was also faster than published averages for academic medical centers (81 vs 103 days). Time to first enrollment was faster for ceding sites versus the non-ceding site, and also faster than published averages (126 vs 149 and 169 days, respectively). Costs were higher than estimates for local institutional review board review and approval. Nearly half (47%) the stakeholders reported being very satisfied or satisfied with the reliance experience, although many noted the challenge related to institutional culture change. Conclusion: Implementation of a single institutional review board represents a shift in practice and culture for many institutions. Evaluation of the reliance arrangements for this study highlights both the potential of, and challenges for, institutions as they transition to single institutional review board review. Although efficiencies were observed for study start-up, we anticipate a learning curve as institutions and research teams implement necessary process and resource changes to adapt to single institutional review board oversight. Findings may inform research teams but are, however, limited by the relatively small number of sites and lack of a control group.